International standards of the right to an adequate standard of living and their impact on Ukrainian legislation - T. I. Gudz; V. V. Maltsev (Law and Safety)
The provisions of international standards of human right to an adequate standard of living and their impact on national legislation have been investigated. It has been emphasized that since Ukraine gained independence and up to now the issue of ensuring a sufficient standard of living has remained one of the most problematic for our state. European integration processes, which provide for the modernization of Ukraine’s socio-economic policy towards improving the quality of life of each person, also increase the need for scientific research. It has been emphasized on the relevance and importance of studying the issues of regulation of the right to an adequate standard of living in view of the existing social problems, which have become much more acute with the beginning of the full-scale war of Russia against our country and have a huge negative impact on the living standards of Ukrainian citizens.